Pathomorphism of central nervous system tuberculosis in school-age children (According to autopsy data) - L. I. Mykolyshin; Z. I. Piskur (Туберкулез и болезни лёгких)
Autopsy protocols for deaths of 7-14-year-old children in 1947 to 2012, which indicated tuberculosis of the central nervous system (CNS), were analyzed; the incidence of the above pathology was 80.3% among 132 children who died from tuberculosis in this period,. It was ascertained that in 1947-1956 the children died from generalized tuberculosis with involvement of CNS and other organs. As a result of induced pathomorphism, the number of autopsies reduced by 13.9 times in 1957-1966 and by 97 times in 1967-1994 as compared to 1947-1956. Changes occurred in the pattern of forms of CNS tuberculosis and the number of autopsied deaths from CNS tuberculosis concurrent with generalized tuberculosis decreased by 16.7 times; there was a decline in the number of affected organs. However, the 1995-2012 deaths from generalized tuberculosis with involvement of CNS and other organs in 7-14-year-old children are suggestive of the reversion of severe tuberculosis and the necessity of intensifying social, preventive, and remedial measures among them.